Auditoría en seguridad vial de la vía Autopista norte de la calle 94 a la calle 153, Bogotá D.C. (2022)
This document contains all the information of the development carried out in the Safety Audit of the North Highway between 94th Street and 153rd Street, where the following variables were reviewed: auscultations, geometric design and signaling, revealing the physical condition of the road and its effects on the road actors that circulate on it, it was thoroughly reviewed through the descriptive quantitative methodology, for this purpose the variables used for each objective were identified, the methods and tools used are presented, the results found are described, from which the sectors with lack of signaling were highlighted. The signaling was evaluated by means of the signaling manual, and the quality of the road with the risk matrix indicator. By establishing the consistency of the design through the information obtained from the field survey and the Signals software, it was possible to corroborate the similarity of the results obtained; therefore, it is considered that there is a consistency between what has been built and the information of the Auto CAD provided by the District Mobility Secretariat (SDM) in 2012